A Midwest Perspective on Biochar Integration in Extension - Blake C. Colclasure; Elizabeth Bose; Jack Dempsey; Taylor K. Ruth (Journal of Human Sciences and Extension)
Biochar can be considered a climate-smart, agricultural soil amendment due to its ability to provide long-term storage of carbon. Research examining the impacts of biochar-enriched soils reported improved soil characteristics often leading to agricultural benefits, especially in nutrient-poor soils. Despite the potential use of biochar in the Midwest, United States, few studies have examined biochar in Extension. This study, guided by the Theory of Reasoned Action, used survey methodology to collect information on Midwest Extension agents’ (n = 125) knowledge, attitudes, and subjective normative beliefs toward biochar. These factors, along with agents’ demographics and perceptions toward sustainable soil amendments, were used to predict agents’ future intent to incorporate biochar in their work-related activity. On average, respondents correctly answered approximately half of 12 true-false statements on biochar. Respondents’ attitudes toward biochar, as well as their perceptions of other agents’ attitudes, were, on average, neutral. Agents held moderate importance in promoting sustainable soil amendments. On average, respondents indicated being neither likely nor unlikely to incorporate biochar in their work-related activity, but high variability was found. A significant model was produced that indicates agents who are more knowledgeable about biochar and view biochar more favorably are more likely to incorporate biochar in future work.